Vatican II—Continuity or Discontinuity? Toward an Ontology of Meaning - Ormerod, Neil (Theological studies, 2010)
The article argues that the debate over continuity/discontinuity at Vatican II is hindered by the descriptive nature of the categories under consideration. To move beyond description and into explanation one must adopt an “ontology of meaning.” The nature of such a shift is illustrated with reference to the work of John Henry Newman, Alasdair MacIntyre, and Bernard Lonergan.